Community-Based Ecotourism Empowerment: Strengthening Local Institutions in Area Branca, Dili, Timor Leste - Rideng, I Wayan; Styawati, Ni Komang Arini; Sugiartha, I Nyoman Gd (International Journal of Community Service (IJCS), 2025)
The Branca Area in Dili City, Timor-Leste, is a coastal zone with great potential for community-based ecotourism development. However, management of this area still faces problems such as weak local institutional capacity, low community participation, limited supporting facilities, and regulatory constraints due to a centralized tourism management system. This international community service activity aims to identify existing conditions, formulate institutional empowerment models, and provide training and assistance through Focus Group Discussions (FGDs). The implementation methods include literature studies, situation analysis, institutional mapping, and the application of technological innovations for promotion and conservation. The results of the activity showed an increase in community capacity, the formation of a simple group structure, increased conservation awareness, and an increase in local economic activity. This activity produced academic outputs in the form of scientific articles, media publications, documentary videos, and a 30% increase in institutional capacity. This programmed emphasizes the urgency of community-based ecotourism (CBET) as a sustainable strategy to improve socio-economic welfare and environmental conservation in Branca